2004
DOI: 10.1124/jpet.104.067603
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Galantamine onN-Methyl-d-Aspartate Receptors in Rat Cortical Neurons

Abstract: Galantamine, a new Alzheimer's drug approved in the United States, is known to inhibit acetylcholinesterase and potentiate acetylcholine-induced currents in brain neurons. However, because both cholinergic and N-methyl-D-aspartate (NMDA) systems are down-regulated in the brain of Alzheimer's patients, we studied the effects of galantamine on NMDA receptors. NMDA-induced whole-cell currents were recorded from the rat multipolar cortical neurons in primary culture. NMDA currents recorded in Mg 2ϩ -free media wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…8 Unlike other AChE inhibitor drugs, 1 has a postulated dual mechanism of action: in addition to inhibiting AChE, 1 has shown a facilitating effect on the nicotinic receptor-mediated transmission via allosteric modulation of the α-subunit of nicotinic receptors. 9 In particular, 1 can enhance synaptic NMDAR activity 10,11 by activating α7 nicotinic receptors located on presynaptic glutamatergic neurons. 12 Working together, 1 and 2 may thus improve neurophysiological responses in AD patients, 13 and their combination might offer a promising therapeutic strategy for AD treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8 Unlike other AChE inhibitor drugs, 1 has a postulated dual mechanism of action: in addition to inhibiting AChE, 1 has shown a facilitating effect on the nicotinic receptor-mediated transmission via allosteric modulation of the α-subunit of nicotinic receptors. 9 In particular, 1 can enhance synaptic NMDAR activity 10,11 by activating α7 nicotinic receptors located on presynaptic glutamatergic neurons. 12 Working together, 1 and 2 may thus improve neurophysiological responses in AD patients, 13 and their combination might offer a promising therapeutic strategy for AD treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Whereas nefiracetam (Moriguchi et al, 2003a,b), galantamine (Moriguchi et al, 2004b), and donepezil (present study) all are capable of modulating the activity of NMDA receptors, their mechanisms of action appear to be different Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…However, galantamine differs from nefiracetam in three aspects (Moriguchi et al, 2004b). First, the effect was much less potent, with the maximum effect occurring at 1 M; second, the receptor affinity for NMDA is increased without change in the maximum saturating responses; and third, there is no interaction with the glycine binding site of the NMDA receptor.…”
Section: Donepezil On Nmda Receptors 131mentioning
confidence: 96%
See 1 more Smart Citation
“…We previously reported that galantamine potentiates NMDAR activity in rat cortical neurons (6). Potentiation of nAChR and enhancement of NMDAR activity may synergistically antagonize deficits in memory and cognitive function in AD.…”
Section: Introductionmentioning
confidence: 99%